An in silico evaluation of lorlatinib as a potential therapy for novel amino acid substitutions in the tyrosine kinase domain of the ALK protein associated with cancer - Zapata Dongo, Richard Junior; Poterico, Julio A.; Fontana, Diletta; Mologni, Luca; Alvarez-Chacon, Carla; Rojas-Armas, Juan; Calla, Jaeson (Frontiers in Pharmacology, 2025)
The anaplastic lymphoma kinase (alk) gene on chromosome 2 encodes a receptor tyrosine kinase protein essential for key signaling pathways regulating cell proliferation and differentiation. Mutations in alk have been implicated in multiple cancers, including non-small cell lung cancer (NSCLC) and anaplastic large cell lymphoma. While ALK inhibitors have demonstrated efficacy in targeted therapies, resistance due to specific amino acid substitutions requires the development of novel therapeutic strategies. This study aims to identify ALK tyrosine kinase domain mutations using data from the Cancer Genome Atlas and to evaluate the potential of lorlatinib, a third-generation ALK inhibitor, in overcoming these mutations. Using the SIFT and Polyphen-2 algorithms, we identified 53 deleterious ALK mutations associated with different newly recognized cancer types. These mutations were subjected to in silico molecular docking with lorlatinib. Our results indicate strong binding affinities (ranging from −9.4 to −10.8 kcal/mol) across all identified mutations, suggesting a significant interaction between lorlatinib and mutated ALK variants. Furthermore, protein-ligand interaction analysis revealed critical hydrophobic interactions, hydrogen bonds, and essential halogen bonds reinforcing lorlatinib as a potential utility in treating a broader spectrum of ALK-positive tumors beyond NSCLC. This research underscores the importance of repurposing in silico drugs and highlights the need for continued exploration of ALK mutations in cancer therapeutics.